Location of the Origin of Transfer of the Sex Factor F - Willetts, N. S. (1972)
The location of the origin of transfer on the map of Flac has been determined by two different techniques. The first showed that no transfer cistrons were transferred early by a transposition Hfr strain with a known point of chromosomal integration into Flac, and the second used a series of transfer-deficient Hfr deletion strains to map a locus required in cis for chromosome transfer by an incoming Flac factor. Both techniques gave results consistent with a location for the origin of transfer between traJ and the φ(R)(11) locus.